Understanding and Targeting the Epigenetic Regulation to Overcome EGFR-TKIs Resistance in Human Cancer - Sun, Lan; Gao, Lingyue; Zhao, Yingxi; Wang, Yuqing; Xu, Qianhui; Zheng, Yiru; Chen, Jiali; Wang, He; Wang, Lihui (Recent Patents on Anti-Cancer Drug Discovery, 2023)
Background: The occurrence and progression of cancer are the results of the dysregulation of genetics and epigenetics. Epigenetic regulation can reversibly affect gene transcription activity without changing DNA structure. Covalent modification of histones is crucial in the epigenetic regulation of gene expression. Furthermore, epidermal growth factor receptor (EGFR) significantly affects cell tumorigenesis, proliferation, antitumor drug resistance, etc. Overexpression of EGFR promotes cancer development. Therefore, EGFR-targeted drugs have become the focus of tumor therapy. With the advent of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), EGFR-TKIs resistance, which occurs about half a year to a year, has become an obstacle in cancer treatment. Objective: The objective of this study is to discuss the ways to overcome EGFR-TKIs resistance in a variety of tumors. Methods: The combination therapy of epigenetic drugs and other drugs is used. Results: The combination of the two drugs can overcome the resistance of EGFR-TKIs and prolong the survival of patients. Conclusion: This article depicts the concepts of epigenetics and the mechanism of EGFR-TKIs resistance and then illustrates the relationship between epigenetic mechanisms and EGFR-TKIs resistance. Finally, it discusses the clinical research and the latest patents for using epigenetic drugs to reverse EGFR-TKIs resistance in human cancer. In the future, more novel targets may be discovered for overcoming resistance to EGFR-TKIs, not just on histone deacetylases (HDACs). The dosing course and mode of administration of the combination therapy containing epigenetic drugs need further study. This review provides new ideas for using epigenetic agents to overcome EGFR-TKIs resistance.
Keywords: EGFR-TKIs